2015
DOI: 10.14393/bj-v31n2a2015-22387
|View full text |Cite
|
Sign up to set email alerts
|

Controle pós-colheita da antracnose do pimentão pela levedura Rhodotorula glutinis

Abstract: RESUMO:Considerando as perdas causadas em pós-colheita pela antracnose no pimentão e à ineficácia das medidas de controle atualmente utilizadas, este trabalho teve por objetivo estudar a potencialidade antagônica in vitro e in vivo de quinze isolados de leveduras à Colletotrichum sp., agente causal da antracnose em pimentão. Foi calculada a porcentagem de inibição do crescimento do fungo dos tratamentos em relação à testemunha nos testes in vitro e determinado o tamanho da área lesionada em frutos através da m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The fungus C. gloeosporioides is the main responsible for anthracnose in fruits of Capsicum in Brazil, and can appear in any part of the plant, from its development in the field to even in fruits stored in the post-harvest phase [26]. Colletotrichum species can infect pepper fruits at any stage of maturation.…”
Section: Resultsmentioning
confidence: 99%
“…The fungus C. gloeosporioides is the main responsible for anthracnose in fruits of Capsicum in Brazil, and can appear in any part of the plant, from its development in the field to even in fruits stored in the post-harvest phase [26]. Colletotrichum species can infect pepper fruits at any stage of maturation.…”
Section: Resultsmentioning
confidence: 99%
“…C.V (coefficient of variation); Means followed by different letters in the column, differ by Tukey's test (p < 0.05). França et al (2015) evaluating the post-harvest control of anthracnose in peppers by the use of R. glutinis observed that this was more effective in controlling the disease when using yeast in post-harvest fruits, assuming that the success of this yeast in the anthracnose control in peppers may be due to the yeast's ability to produce enzymes such as pectinases, chitins and glucanases (Saravanakumar et al, 2009;Bauermaister et al, 2010), responsible for depolymerizing the cell wall of certain fungi, as well as competition for nutrients. According to Silva et al (2014), among the treatments based on use of antagonists, R. glutinis also presented a satisfactory result in the control of the sweet rot of pepper.…”
Section: Production Of Volatile and Non-volatile Compounds By Yeast And Conidia Germinationmentioning
confidence: 99%
“…The other yeasts do not differ significantly from the control. França et al (2015), found that the most efficient responses in the control of Colletotrichum gloeosporioides in pepper culture were from isolates belonging to the species R. glutinis, with growth inhibition up to 47.99%, being the control mechanisms competition for space and nutrients, production of antibiotics and also for parasitism.…”
Section: Production Of Volatile and Non-volatile Compounds By Yeast And Conidia Germinationmentioning
confidence: 99%
“…Nessa perspectiva a antracnose, doença causada por fungos do gênero Colletotrichumé uma das doenças de maior importância para as solanáceas como o pimentão (Capsicum annum) [de França et al 2015]. A antracnose pode atingir todos os estágios de desenvolvimento da planta, desde mudas no viveiro até os frutos após a colheita [de Azevedo et al 2006].…”
Section: Introductionunclassified